Analysis of Regional Economic Potential and Competitiveness in North Lombok Regency - Muh Husnan Hadi; Wahyunadi Wahyunadi; Emi Salmah (JURNAL ECONOMINA, 2026)
This study aims to analyze the economic potential, competitiveness, growth prospects, and formulate the implications of regional economic development policies in North Lombok Regency. The research method used is a quantitative descriptive-analytical method by utilizing secondary data of Gross Regional Domestic Product (GRDP) of North Lombok Regency and West Nusa Tenggara Province. The analysis techniques used include Location Quotient (LQ) to identify basic and non-basic sectors, Dynamic Location Quotient (DLQ) to see the potential for future sector growth, Shift Share (SS) to measure sectoral competitiveness, and Klassen Typology to group sectors based on economic contribution and growth. The results of the study indicate that the basic sectors in North Lombok Regency are dominated by the accommodation and food and beverage provision sector, agriculture, electricity and gas procurement, water supply and waste management, trade, construction, real estate, corporate services, government administration, education, and other services. Furthermore, the DLQ results show that most sectors have good growth prospects, especially the utilities sector, financial services, and other services. Meanwhile, the Shift Share analysis shows that the accommodation and food and beverage sector, financial services, and several other service sectors have positive competitiveness. Based on the Klassen Typology, the main leading sectors are in the advanced and rapidly growing quadrant, while several sectors, such as mining, transportation, information and communications, and healthcare, are still lagging behind. Therefore, regional development policies need to be directed at strengthening leading sectors, revitalizing potential sectors, and accelerating the development of underdeveloped sectors to create a balanced, competitive, and sustainable economic structure